2007
DOI: 10.1007/s11255-006-9161-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms, prostate volume, uroflowmetry, residual urine volume and bladder wall thickness in Turkish men: a comparative analysis

Abstract: BWT seems to be significantly increased in men who have Q (max) values smaller than 10 ml/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…15 In another study, researchers found that BWT was higher in patients with a Qmax <10 mL/s and no significant relationship between BWT and IPSS. 16 Our findings demonstrated a mean BWT of 5.25 ± 1.76 in all patients. The mean BWT of Group 1 was 3.72 ± 0.56 and Group 2 was 6.43 ± 1.13.…”
Section: Karakose Et Alsupporting
confidence: 51%
“…15 In another study, researchers found that BWT was higher in patients with a Qmax <10 mL/s and no significant relationship between BWT and IPSS. 16 Our findings demonstrated a mean BWT of 5.25 ± 1.76 in all patients. The mean BWT of Group 1 was 3.72 ± 0.56 and Group 2 was 6.43 ± 1.13.…”
Section: Karakose Et Alsupporting
confidence: 51%
“…With the probe parallel to just above the symphysis pubis of the patient, an image of the largest circumference of the prostate was captured on the screen. The prostate volume was estimated from the diameters of the minor axis and the major axis using an elliptical, 3-axis volume formula (10). PVR was measured immediately after voiding with a 3.5-MHz curvilinear ultrasound array.…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, studies started to be published revealing the predictive value of DWT in men with BOO (7,9,10,12). In 2007, Kessler et al (12) found a significant correlation between DWT and pressure flow studies (PFS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Bladder wall thickening and bladder mass increase have been noticed among men with LUTS in multiple studies. 13-15 …”
Section: Introductionmentioning
confidence: 99%